Nurturing Muslims in Confucian Cradle: A historical overview of Islamic Religious education in China - Qurrat ul Ain, Ayesha (Journal of Islamic and Religious Studies, 2020)
The identity negotiation among a religious ethnic minority is closely tied with its religious educational system and it equally applies to the case of the Sino-Muslim community. This paper investigates that how did Muslim religious educational system stature the distinctiveness of Muslim ethnic minority in the Chinese context while simultaneously helping them integrate into the Chinese society and what role did it play in placing Muslims at a continuum between Chinese and Islamic educational spheres. It contends that Chinese Islamic education predominantly adapted the essential characteristics of the Islamic madrasa system to the requirements of the Muslim population living in a Confucian social order. Hence it is a true reflection of the cultural simultaneity of Chinese Muslims. The research employs ethnographic methodologies including participant observation and extensive interviewing and relies upon the archival data for the historical contextualization of the observed facts. It concludes that the Islamic educational system in China played an inevitably crucial role in the survival of Islamic faith and knowledge in the Chinese land. On one hand, it connected the Chinese Muslim community with the mainstream Muslim world transcending regional and cultural boundaries and on the other hand, its certain features remained exclusive to Chinese Muslim civilization indicating the dynamic and vigorous interrelationship between Confucian and Islamic educational systems.